2022
DOI: 10.3390/molecules27217508
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Formation of 1,2,4-Oxadiazine Core in Reaction of Amidoximes with Maleic or Fumaric Esters

Abstract: We have developed a simple and convenient method for the synthesis of 3-aryl- and 3-hetaryl-1,2,4-oxadiazin-5-ones bearing an easily functionalizable (methoxycarbonyl)methyl group at position 6 via the reaction of aryl or hetaryl amidoximes with maleates or fumarates. The conditions for this reaction were optimized. Different products can be synthesized selectively in good yields depending on the base used and the ratio of reactants: substituted (1,2,4-oxadiazin-6-yl)acetic acids, corresponding methyl esters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Recently, Boyarskiy with coworkers reported that the reaction between amidoximes and maleic esters in NaOH/DMSO medium provided 1,2,4-oxadiazin-5(6 H )-ones instead of the expected 1,2,4-oxadiazoles ( Scheme 17 ). The base replacement to t -BuONa and increasing the amidoxime amount up to 2.5 eq allowed them to obtain hybrid 3-(aryl)-6-((3-(aryl)-1,2,4-oxadiazol-5-yl)methyl)-4 H -1,2,4-oxadiazin-5(6 H )-ones [ 112 ].…”
Section: Base-induced Cyclodehydration Of O -Acyla...mentioning
confidence: 99%
“…Recently, Boyarskiy with coworkers reported that the reaction between amidoximes and maleic esters in NaOH/DMSO medium provided 1,2,4-oxadiazin-5(6 H )-ones instead of the expected 1,2,4-oxadiazoles ( Scheme 17 ). The base replacement to t -BuONa and increasing the amidoxime amount up to 2.5 eq allowed them to obtain hybrid 3-(aryl)-6-((3-(aryl)-1,2,4-oxadiazol-5-yl)methyl)-4 H -1,2,4-oxadiazin-5(6 H )-ones [ 112 ].…”
Section: Base-induced Cyclodehydration Of O -Acyla...mentioning
confidence: 99%